APPROPRIATE EMPIRICAL MANAGEMENT OF MICROBIAL INFECTIONS IN A TERTIARY CARE HOSPITAL: A COST- EFFECTIVENESS APPROACH. - N, Onchari Divinah; Simon, Josin Mary; Tomy, Sneha; R, Arun Prasath; V, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Antibiotics are mostly prescribed empirically to decrease health-care costs. This has led to the misuse of antibiotics thereby making them inefficient in the treatment of infections. The aim of this study was to determine the appropriate, cost-effective drug for the empirical therapy in microbial infections. Methods: A prospective observational study was conducted for a period of 6 months. Cost-effectiveness ratio (CER) of these antibiotics prescribed was calculated to determine the cost-effective drugs for the common microorganisms and common infections. Results: In a population of 205 patients, 54.6% were treated based on antibiotic sensitivity pattern whereas 45.3% were treated empirically. In known microbial infections, the prevailing microorganism was extended-spectrum beta-lactamase (ESBL) producing Escherichia-coli (14.3%), Staphylococcus aureus (10.6%), Pseudomonas aeruginosa (9.8%), Klebsiella pneumonia (9.8%), and K. pneumoniae ESBL (6.81%). Based on the CER, the most cost-effective drugs for these organisms were found to be ciprofloxacin, clindamycin, ofloxacin, levofloxacin, and amikacin, respectively. In unknown microbial infection (empirical treatment), Diabetic Foot Infection (DFT) (25.8%), respiratory tract infection (RTI) (23.6%), and urinary tract infection (UTI) (16.1%) were the most common infections. The most cost-effective drugs for these infections were clindamycin, levofloxacin, and azithromycin, respectively. The predominant microorganism in DFT was found to be S. aureus (71%), in UTI was found to be E. coli ESBL (52%), and in RTI were found to be P. aeruginosa (42.4%) and K. pneumonia (32.3%). Conclusion: Appropriate empirical antibiotic treatment is associated with a lower medical cost and a better success rate in patients with microbial infections.